Adaptive services reconfiguration in manufacturing environments using a multi-agent system approach - Rodrigues, Nelson (2017)
The era of mass customization of goods forces manufacturing systems to promote agility, flexibility and responsiveness, leading to complex and unpredictable systems. Such challenges have an impact in terms of the system responsiveness and adaptation, production costs, product quality, etc. In order to improve those aspects, some flexible control manufacturing paradigms were proposed offering elasticity to change available skills and provide new services. However, the understanding of when and how to (self-) reconfigure the system aiming to perform a fast changeover, is a crucial issue. This work proposes a self-organizing multi-agent system approach for an efficient and on the fly reconfiguration of services in the manufacturing domain. Besides self-organizing techniques, other dimensions, e.g., “social-based” trust and QoS metrics, are used to ensure a constant QoS in an agile production system. The insertion of intelligent agents facilitates the improvement of strategies that perform the service reconfiguration, and in addition, permits to understand when and how self-reconfiguration takes place in order to allow a continuous improvement of the system performance. Additionally, this work addresses solutions for real industrial applications, being aligned with some characteristics of the Industrie 4.0 initiative, namely the distributed intelligence and self-* methods, e.g. self-adaptation, self-organization and self-configuration